Toward automatic adjustment of pointing device configuration to accommodate physical impairment. - Lopresti EF; Koester HH; Simpson RC (Disability & Rehabilitation: Assistive Technology, 2008)
Purpose. Software was developed which makes recommendations regarding configuration of a computer pointing device, such as a mouse, to accommodate a person's physical impairment. Specifically, a software agent automatically recommends a setting for the computer's control-display gain based on observations of a user's performance in a target selection task. Method. The software agent makes its recommendations based on available adjustment settings in the existing operating system. The agent was evaluated in studies with 12 participants who have motor impairments. Results. The agent-selected gain was not associated with significant improvements in selection time or error-free performance compared with the operating system's default gain. Across participants and trials, gain did not have a significant effect on selection time except at the lowest gain settings tested. However, two participants did have notable and consistent improvement in selection time and error-free performance using the agent-selected gain; gain across trials had a significant effect on number of target entries and number of submovements; and a post-hoc analysis indicated improved target selection time when varying both target size and control-display gain. Conclusion. These observations provide possible avenues for future work, although the current study indicates that changes to control-display gain, alone, are unlikely to offer improvements in speed or accuracy for the general population of people with motor impairments.